Choosing wisely: A prospective study of direct to operating room trauma resuscitation including real-time trauma surgeon after-action review. Issue 2 (August 2021) - Martin, Matthew J.; Johnson, Amelia; Rott, Michael; Kuchler, Andrea; Cole, Frederick; Ramzy, Ameen; Barbosa, Ronald; Long, William B.
Abstract : INTRODUCTION: Although several centers have direct to operating room (DOR) resuscitation programs, there are no published prospective studies on optimal patient selection, interventions, outcomes, or real-time surgeon assessments. METHODS: Direct to operating room cases for 1 year were prospectively enrolled. Demographics, injury types/severity, triage criteria, interventions, and outcomes including Glasgow Outcome Scale score were collected. Detailed time-to-event and sequence data on initial lifesaving interventions (LSIs) or emergent surgeries were analyzed. A structured real-time attending surgeon assessment tool for each case was collected. Direct to operating room activation criteria were grouped into categories: mechanism, physiology, injury pattern, or emergency medical services (EMS) suspicion. RESULTS: There were 104 DOR cases: male, 84%; penetrating, 80%; and severely injured (Injury Severity Score, >15), 39%. The majority (65%) required at least one LSI (median of 7 minutes from arrival), and 41% underwent immediate emergent surgery (median, 26 minutes). Blunt patients were more severely injured and more likely to undergo LSI (86% vs. 59%) but less likely to require emergent surgery (19% vs. 47%, all p < 0.05). Analysis of DOR criteria categories showed unique patterns in each group for interventions and outcomes, with EMS suspicion associated with the lowest need for DOR. Surgeon assessment tool results found that DOR was indicated in 84% and improved care in 63%, with a small subset identified (9%) where DOR had a negative impact. CONCLUSION: Direct to operating room resuscitation facilitated timely emergent interventions in penetrating truncal trauma and a select subset of critically ill blunt patients. Unique intervention/outcome profiles were identified by activation criteria groups, with little utility among activations for EMS suspicion. Real-time surgeon assessment tool identified high- and low-yield DOR groups. LEVEL OF EVIDENCE: Prospective observational study, level III. Abstract : Supplemental digital content is available in the text.